1985
DOI: 10.1172/jci111789
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody to human platelet glycoprotein IIIa detects a related protein in cultured human endothelial cells.

Abstract: We have previously described a series of monoclonal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…Membrane proteins similar to GP Ilb-Ila are found in white blood cells (40) and endothelial cells (41,42); TSP is synthesized and secreted by monocytes (43) and endothelial cells (44); and GMP-140 is present in endothelial cells (45). Therefore in whole blood, these antigens may not be only derived from platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane proteins similar to GP Ilb-Ila are found in white blood cells (40) and endothelial cells (41,42); TSP is synthesized and secreted by monocytes (43) and endothelial cells (44); and GMP-140 is present in endothelial cells (45). Therefore in whole blood, these antigens may not be only derived from platelets.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Thiagarajan et al (33) used both a monoclonal and a polyclonal antibody, each having specificity for only GPUIa, to detect a related protein in endothelial ceils. Though these authors suggested that a GPl/b-like molecule was unlikely to be present in cultured endothelium, their argument was in part based upon their unpublished observations that the anti-platelet GPllb-specific monoclonal antibody, Tab (19,20), was unreactive with endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the resuits shown in Figs. 1 and 2, we adopted the convention suggested by Thiagarajan et al (33) to term the endothelial cell analogue of platelet GPIIb-IIIa, EC GPIIb, and EC GPffla, respectively.…”
Section: Identification Of Platelet Membrane Gpiib and Gpiiia Analogumentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to the nearly 1 ϫ 10 6 molecules of PECAM-1 present on their cell surface (24), HUVECs also express 100,000 copies of the integrin ␣ v ␤ 3 (25) as well as abundant levels of heparan sulfate and chondroitin sulfate (26,27). ␣ v ␤ 3 has previously been shown not to be involved in PECAM-1 proteoliposome (14) or PECAM-1/IgG (19) binding.…”
Section: Interaction Of Pecam-1/igg With Cells Correlates With Cellmentioning
confidence: 99%